Evaluation of leflunomide for the treatment of BK viremia and biopsy proven BK nephropathy; a single center experience - Nicole Nesselhauf; Jaclyn Strutt; Bahar Bastani (Society of Diabetic Nephropathy Prevention, 2016)
Background: BK virus reactivation is a significant complication following renal transplantation that can result in graft failure. Reduction of immunosuppression and substitution of leflunomide for mycophenolate mofetil (MMF) has been used to treat this entity. Objectives: To evaluate the use of leflunomide in BK viremia (BKV) and biopsy proven BK nephropathy (BKN) in kidney and kidney-pancreas transplant recipients. Patients and Methods: We retrospectively reviewed 28 kidney and kidney-pancreas transplant recipients who had received leflunomide for BKV from January 2006 to November 2012. Demographics, time to BKV diagnosis, biopsy findings, rejection episodes, and laboratory data were recorded. Results: The average (mean ± SD) time to BKV from time of transplant was 316.1 ± 368.0 days (62-1708 days). At time of diagnosis, 64% of patients had their maintenance immunosuppression reduced. The indications for leflunomide administration were; BKV and biopsy proven acute rejection (BPAR) (50%), biopsy proven BKN (18%), or persistent BKV (25%). Therapeutic levels (50-100 mcg/mL) were achieved in only 54% of patients, and 60% of them had required a leflunomide dose of at least 60 mg/day. BK virus was cleared from the serum on average of 151 ± 145.2 days (17-476 days). At study commencement, 29% of patients had remained on leflunomide due to persistent BKV. Conclusions: In our study, most patients required at least a 60 mg daily dose of leflunomide to achieve therapeutic levels and to clear the virus compared to the standard 40 mg daily dose. Delaying therapy may result in progressive BKV and BKN.